PENGARUH PENERAPAN MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VII SMP NEGERI 7 PADANG - Rahmatunnisa, Nadya (Jurnal Edukasi dan Penelitian Matematika, 2023)
Mathematics education has a main goals is for students to have problem-solving abilities. However, students’ mathematical problem-solving skills are still low due to teacher-centered learning approaches. The proposed solution is to implement the Creative Problem-Solving instructional model, and therefore, this study is aimed to figure out the impact on mathematical problem-solving abilities by using the CPS instructional model. Quasy Experiment is the research method that employed with a design known as the Nonequivalent Posttest Only Control Group Design. All 7th-grade students at SMP Negeri 7 Padang during the 2022/2023 academic year is the population, and there were two samples. This study using an instrument which is a final test. Using the outcomes of the hypothesis test from the conclusive examination acquired a p-value was 0.000 (0,05), which indicates rejecting the null hypothesis (. It was discovered that there is an impact on students' mathematical problem-solving abilities in class VII at SMP Negeri 7 Padang by using the CPS instructional model.Keywords– Problem-solving abilities, creative problem solving learning model, convensional learning model